Is there space for an industry focused research in academia? I. What can academia offer - López de Cerain, Adela (Spanish Journal of Environmental Mutagenesis and Genomics, 2023)
The main objective of the University is to educate future professionals and society leaders, to investigate and to generate new knowledge that fosters the progression of science. In the field of health sciences, the University is involved in the education of future doctors, pharmacists, chemists, biochemists and biotechnologists, some of which will integrate into multidisciplinary research teams of Universities, research centres and hospitals. In recent years, clinical research within the National Health System (SNS) has been potentiated through Health Research Institutes. Since the early beginning of the 21-st century and up to the year 2008, all markers of R&D in the biomedical field have increased in Spain, both in the public and private sectors. The objective of the pharmaceutical industry is to investigate, develop, produce and commercialize drugs that can alleviate health conditions and cure diseases. It is a business sector that invests in R&D, invigorates biomedical research and contributes to the continuous education of health professionals. The relationship between University and Industry is pivotal for the achievement of their corresponding objectives as their activities are complementary to each other. In terms of biomedical research, scientific progression requires a super-specialization achievable in a few number of research groups. New therapeutic targets, patient segmentation based on genetic properties in order to test increasingly personalized pharmacological treatments, efficacious biotechnological medicinal products with new challenges for safety assessment are some representative examples. In terms of education, the University has to adapt their degree and post-degree educative programs to the needs of the pharmaceutical sector, with a demand for highly skilled professionals, without abandoning aspects of integral student education for them to become free and non-manipulated persons with criteria and ethical sense. What can the University offer to the pharmaceutical industry a) Future professionals: the University is a quarry and should be close to Industry. b) New ideas, treatments and approaches: biomedical research should be focused on solving the problems of diseased persons and preserving human health without conditions. However, once the idea is mature and the clinical application seems feasible then the pharmaceutical industry should take the lead for its development. c) Possible start-up of companies and support during the initial phases, thereby contributing to the economic growth and development of the business sector.